DESIGN AND IMPLEMENTATION IMAGE BASED VISUAL SERVOING ALGORITHM ON ADEPTONE SCARA ROBOT - ILHAMDI RUSYDI (NIM 23204307), MUHAMAD
In this report, we explained about Image Based Visual Servoing system that implemented on Scara AdeptOne Robot with CMU Cam2 camera using SKRBV-2D. It is designed based on Lyapunov stability law on dynamic robot and image model through Robot Jacobian and Image Jacobian matrices sets. Simulation results show the algorithm works properly by setting controller gain constant, K, and the distance depth between object and camera, Z. With K=0.18 and Z=1 system reaches steady state condition at t=25 seconds with pixel error=0 in tracking point object. With K=0.18 and Z=1 system reaches steady state condition at t=6.99 seconds with pixel error=0 in trakcing areal object. Gain of K value produces bigger oscillation before reaching the stable condition. Adding the depth distance (Z) makes system reach steady state condition faster but less accurate because many object pixel value coordinate rounding off.